THE USE OF COMMUNITY LANGUAGE LEARNINGMETHOD TO IMPROVE STUDENTS’ SPEAKING ACHIEVEMENT - Eko Widoyo Putro; Berlin Sibarani (Universitas Negeri Medan, 2015)
This study is aimed at improving the second grade of students’ speakingachievement by using Community Language Learning (CLL) Method. Theresearch was conducted by applying classroom action research. The subject of this study was second grade of Private Senior High School (Sekolah Menengah Atas Swasta) of Dwi Tunggal Tanjung Morawa which consisted of 31 students. To collect the data, the instruments used were primary data (SpeakingTest) and secondary data (interview sheet, observation sheet, field notes). It can be seen from the score in test I, test II and test III. In the Test I, the mean of the students’score was (64.77), in the Test II was (71.35), and the mean of the students’ score of the Test III was (80.90). Based on the interview, and observation sheet, it shows that the expression and excitement of the students got improved as well. It was found that teaching of speaking by using Community Language Learningcould significantly improve students’ speaking achievement.Key Words: Community Language Learning, Method, Improvement, Speaking Achievement